INKUBAKTOR PENETAS TELUR OTOMATIS BERBASIS FUZZY LOGIC CONTROL - Arjunas Asna Anugerah Asna Anugerah; Arnisa Stefanie (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2023)
ABSTRACT The development of technology in today's era has had a profound impact on people's lives. One of them is the creation of an egg incubator. However, the existing egg incubator still uses a simple concept with several weaknesses, including still using the on/off method on the switch, the temperature level required for eggs to hatch is still low, and a manual schedule for egg reversal is still needed. intends to make a research entitled